The Digitalization of Religion: Smartphone Use and Subjective Well-Being during COVID-19 - Muralidharan, Sidharth (Journal for the scientific study of religion, 2023)
Previous findings indicate that smartphone use can decrease life satisfaction and can negatively impact religious or spiritual goals. But since the start of the COVID-19 pandemic, smartphones have become significantly more positive and useful. Smartphones have helped people move on with their lives, especially due to the myriad benefits they offer. Users can “virtually” spend time with family and friends (i.e., social) and can order groceries, read the news, attend to religious and spiritual needs, and entertain themselves (i.e., process) without venturing out. In the theoretical framework of uses and gratifications, we explored the impact that smartphone use can have on the subjective well-being of Jews and Christians, respectively, in countries with the highest smartphone penetration: Israel and the United States. Furthermore, we introduced religiosity and spirituality, which have surged during the pandemic, as mediators in the proposed model. In the United States, social and process smartphone use enhanced subjective well-being through religiosity (vs. spirituality). In Israel, the process use enhanced subjective well-being through spirituality (vs. religiosity). Theoretical implications are discussed.